Effects of platinum loading on the performance of proton exchange membrane fuel cells with high ionomer content in catalyst layers - Ahn, Sang Hyun; Jeon, Sunyeol; Park, Hee-Young; Kim, Soo-Kil; Kim, Hyoung-Juhn; Cho, EunAe; Henkensmeier, Dirk; Yoo, Sung Jong; Nam, Suk Woo; Lim, Tae-Hoon; Jang, Jong Hyun (Pergamon Press Ltd., 2013)
The effect of Pt loading on the performance of proton exchange membrane fuel cells with atmospheric air feed was evaluated at various relative humidities. The membrane electrode assemblies (MEAs) were fabricated by decal methods with high Nafion ionomer content (30 and 40 wt.%). When the Pt loading was decreased, the performance of the MEAs with an ionomer content of 30 wt.% gradually decreased, mainly due to the insufficient active Pt surfaces with low proton conductivity. With a higher ionomer content of 40 wt.%, the activation overpotential was not significantly increased by the decrease in Pt loading, and the concentration overpotential could be largely reduced by decreasing the Pt loading to 0.25 mg/cm(2). When the Pt loading was further decreased to 0.15 mg/cm(2), even though the flooding became more severe, the cell performance at 0.6 V and intermediate relative humidity of 55% was about 71.6%, compared to the MEA with a high Pt loading of 0.35 mg/cm(2) (ionomer content: 30 wt.%). The cell performance could be further enhanced by decreasing the ionomer content in the anode to enhance the water back diffusion. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.